Action of heparin on lecithin:cholesterol acyltransferase activity in normal subjects (Revista Española de Fisiología, 1976)
The triglyceride decrease and free fatty acid increase by lipoproteinlipase post-heparin effect does not modify the Lecithin:Cholesterol Acyltransferase activity in vitro, using homologous substrate, in normal subjects. These findings agree with the unmodified proportion of esterified cholesterol and relative proportion of phospholipids on thin layer chromatographic fractioning after heparin. The conclusion is reached that heparin has no action on Lecithin:Cholesterol Acyltransferase activity in normal subjects.